2010
DOI: 10.1016/j.stem.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Genotype Is an Important Determinant in Identification of Lung Cancer Propagating Cells

Abstract: Successful cancer therapy requires the elimination or incapacitation of all tumor cells capable of regenerating a tumor. Therapeutic advances therefore necessitate the characterization of the cells that are able to propagate a tumor in vivo. We show an important link between tumor genotype and isolation of tumor-propagating cells (TPCs). Three mouse models of the most common form of human lung cancer each had TPCs with a unique cell surface phenotype. The cell surface marker Sca1 did not enrich for TPCs in tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 26 publications
3
112
0
Order By: Relevance
“…Similarly, stem-like cancer cells have been reported in human cancers of the prostate [87][88][89][90][91][92][93][94][95][96][97][98][99][100], lung [101][102][103][104][105][106][107][108][109][110][111], and many other organs (liver, pancreas, kidney, bladder, ovary, etc). In prostate cancer, tumor-initiating cells have been identified in xenografts in CD44 + [90,96], CD44 + α2β1 + [91], TRA-1-60 + CD151 + CD166 + [99], and ALDH + [97,98] populations as well as in SP [87] and holoclones [94].…”
Section: Csc Heterogeneitymentioning
confidence: 69%
See 1 more Smart Citation
“…Similarly, stem-like cancer cells have been reported in human cancers of the prostate [87][88][89][90][91][92][93][94][95][96][97][98][99][100], lung [101][102][103][104][105][106][107][108][109][110][111], and many other organs (liver, pancreas, kidney, bladder, ovary, etc). In prostate cancer, tumor-initiating cells have been identified in xenografts in CD44 + [90,96], CD44 + α2β1 + [91], TRA-1-60 + CD151 + CD166 + [99], and ALDH + [97,98] populations as well as in SP [87] and holoclones [94].…”
Section: Csc Heterogeneitymentioning
confidence: 69%
“…Similarly, CD133 + and CD133 -glioma cells may have different cells-of-origin [70]. There is evidence that the primary tumor genotypes dictate the overall phenotypes of tumor progenitors [44,66,110]. It is conceivable that more mature tumor-initiating cells derived from the primitive CSCs may sustain secondary genetic hits and in turn become new CSCs, and then develop independently of the original CSCs.…”
Section: Csc Heterogeneitymentioning
confidence: 99%
“…This is in contrast to recent claims that, in K-Ras and epidermal growth factor receptor (EGFR) models, 1 in 10,000 cells are tumor initiating (28). Although it is possible that Jenv tumors are fundamentally different than those driven by other oncogenes, it seems likely that tumor-initiating cell frequency is vastly underestimated in the aforementioned models.…”
Section: Discussionmentioning
confidence: 60%
“…However, although the previous study showed that 100% of lineage Recent reports suggest that one of the BASC markers, Sca-1, does enrich for tumor-propagating activity in mouse NSCLC, but this result is dependent on the nature of the primary oncogenic lesion (28). Interestingly, Sca-1 expression identified CSC in K-ras G12D /p53 À mice, but not in K-ras G12D alone or EGFR T790M-L858R -activated oncogene mouse models.…”
Section: Discussionmentioning
confidence: 89%
“…(59) Co-expression of CD133 and a6-integrin was observed in some but not all tumors. The genetic mutation profile may also influence the nature and phenotype of CSCs, as suggested by studies on different genetic mouse models of lung adenocarcinoma (60), whereas epigenetic changes in regulatory genes could impact marker expression itself. (64).…”
Section: Csc Conceptmentioning
confidence: 99%